STUDI FAKTOR PEMANFAATAN DAN LIMBAH PEMANENAN KAYU DI HUTAN ALAM PAPUA BARAT - Soenarno; Wesman Endom; Sona Suhartana (BRIN Publishing, 2018)
Timber harvesting is an important process in timber utilization because it determines the quality of log. Two important things in timber harvesting are recovery rate and residual factors. This paper identifies distribution, forms and condition of harvesting waste as well as determines utilization factors and timber residual factor due to timber harvesting. Research was conducted in two areas of forest management in Wasior and Nabire Districts, West Papua Province. Recovery rate of forest concession with Reduced Impact Logging (RIL) techniques tend to be higher than that of conventional techniques. Recovery rate ranged from 86.3–87.8% with an average of 86.9% and residual factor ranged from 12.3–13.8%, with the average of 13.1%. The average utilized wood amounted of 4.578 m3/tree from the potential clear bole of 5.293 m3/tree. The wasted volumes ranged from 0.548 to 0.664 m3/tree with an average of 0.564 m3/tree. In general, most of the logging waste was in the form of wood defects (65.1%), broken (23.3%) and firm timber waste (11.6%) which represented the lowest percentage.